Dynamics of Mismatch and Alternative Excision-Dependent Repair in Replicating Bacillus subtilis DNA Examined Under Conditions of Neutral Selection - Patlán-Vázquez, Adriana G.; Ayala-García, Víctor M.; Vallin, Carmen; Cortés, Jonathan; Vásquez-Morales, Suria G.; Robleto, Eduardo A.; Nudler, Evgeny; Pedraza-Reyes, Mario (Frontiers in Microbiology, 2022)
Spontaneous DNA deamination is a potential source of transition mutations. In Bacillus subtilis, EndoV, a component of the alternative excision repair pathway (AER), counteracts the mutagenicity of base deamination-induced mispairs. Here, we report that the mismatch repair (MMR) system, MutSL, prevents the harmful effects of HNO2, a deaminating agent of Cytosine (C), Adenine (A), and Guanine (G). Using Maximum Depth Sequencing (MDS), which measures mutagenesis under conditions of neutral selection, in B. subtilis strains proficient or deficient in MutSL and/or EndoV, revealed asymmetric and heterogeneous patterns of mutations in both DNA template strands. While the lagging template strand showed a higher frequency of C → T substitutions; G → A mutations, occurred more frequently in the leading template strand in different genetic backgrounds. In summary, our results unveiled a role for MutSL in preventing the deleterious effects of base deamination and uncovered differential patterns of base deamination processing by the AER and MMR systems that are influenced by the sequence context and the replicating DNA strand.